The implementation of Canva as a digital learning tool in English learning at vocational school - Sugiarni; Widiastuti, Dina Eka; Tahrun (Universitas Muhammadiyah Malang, 2024)
This study aims to investigates the implementation of Canva as a digital learning tool at SMKN 1 Parit Tiga in West Bangka. Canva, a versatile graphic design platform, offers various features for creating visually appealing materials. This study used qualitative approach, using a case study design. It explores how Canva enhances teaching and learning processes, engages students, and improves learning outcomes in a vocational high school setting. The data collection was done through interviews, classroom observations, and document analysis. The data, then, were analyzed using thematic analysis. The research findings highlight the seamless integration of Canva into lesson planning, teachers' motivations for using Canva, and the positive impact on student engagement and creativity. The results indicated that Canva significantly increases student interest, engagement, and confidence, leading to enhanced creativity and understanding of topics. Recommendations include providing professional development opportunities for teachers and incorporating student feedback to optimize Canva's use in the classroom. Overall, the study underscores the promising results of integrating Canva into educational settings to enhance student motivation, creativity, and collaboration.